Lifespan Extension in Long-Lived Vertebrates Rooted in Ecological Adaptation - Omotoso, Olatunde; Gladyshev, Vadim N.; Zhou, Xuming (Frontiers in Cell and Developmental Biology, 2021)
Contemporary studies on aging and longevity have largely overlooked the role that adaptation plays in lifespan variation across species. Emerging evidence indicates that the genetic signals of extended lifespan may be maintained by natural selection, suggesting longevity could be a product of organismal adaptation. The mechanisms of adaptation in long-lived animals are believed to account for the modification of physiological function. Here, we first review the recent progress in the comparative biology of long-lived animals, together with the emergence of adaptive genetic factors that control longevity and disease resistance. We then propose that hitchhiking of adaptive genetic changes is the basis for lifespan changes and suggest ways to test this evolutionary model. As each adaptive or adaptive-linked mutations/substitutions generate specific forms of longevity effects, the cumulative beneficial compensation is largely non-random and is indirectly favored by natural selection. We consider this concept in light of other proposed theories of aging and integrate these disparate ideas into an adaptive evolution model, highlighting evolutionary strategies in decoding genetic factors of aging.